Football Player Position Decision Support System Using MOORA - Huwanda Hamidah; Hari Antoni Musril; Supratman Zakir; Gusnita Darmawati (Ali Institute of Research and Publication, 2026)
This study aims to design a decision support system to determine football player positions objectively in extracurricular activities at SMA N 1 Matur. The main problem is that player positioning is still determined subjectively based on the coach’s observations, resulting in less optimal placement. This research used the Research and Development (R&D) method with the Agile development model. The system was developed as a web-based application using PHP and MySQL, while the MOORA method was applied to calculate and determine player positions based on several assessment criteria. System testing referred to the ISO/IEC 25010 standard, including functional suitability, compatibility, and usability aspects. The testing results showed that functional suitability and compatibility achieved 100%, while usability obtained a score of 0.928 in the very feasible category. The system validity result reached an average score of 0.938, and the system calculation results were consistent with manual calculations. The novelty of this study lies in the implementation of the MOORA method in a web-based decision support system to determine football player positions more objectively and systematically.